Modified Design of Two-Switch Buck-Boost Converter to Improve Power Efficiency Using Fewer Conduction Components - Sunghwan Kim; Haiyoung Jung; Seok-hyun Lee (Applied Sciences, 2022)
In this study, a modified design of a two-switch buck-boost (TSBB) converter is proposed to improve power efficiency using fewer conduction components, and the optimal power range is measured. The proposed TSBB converter operates in three topologies: buck, boost, and buck-boost, like the conventional TSBB converter. However, the proposed converter improves the power efficiency in the buck and buck-boost topologies by decreasing conduction loss using the diode in the switch-off section while maintaining the same number of semiconductors as that in the conventional TSBB converter. The power efficiency of the buck topology improves for the power range 10–80 W in the constant voltage (CV) and constant current (CC) modes; it increases on average by 0.75–1.36% and 0.83–2.27% in the CV and CC modes, respectively. The power efficiency of the buck-boost topology step-down improves for the 10–80 W in all modes. This increases the average by 0.73–0.99% and 3.33–4.75% in the CV and CC modes, respectively. The power efficiency of the buck-boost topology step-up increases on average by 1.65–2.00% for 10–80 W in the CV mode. In the CC mode, it increases by 2.17–2.77% on average for 10–50 W.